Soybean hulls and alfalfa for limit-fed cattle - Trater, A.M.; Löest, C.A.; Lambert, B.D.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the optimal level of alfalfa inclusion in limit-fed, soybean hull-based diets. Steers were fed soybean hull-based diets containing 0 to 30% alfalfa or alfalfa alone. Feed intakes were lower for alfalfa than for soybean hull-based diets. Digestibilities of dry matter and neutral detergent fiber were lower (P<0.05) for alfalfa than for diets containing soybean hulls. Dry matter and neutral detergent fiber digestibilities were similar for different levels of alfalfa in diets containing soybean hulls, although there were positive associative effects between soybean hulls and alfalfa. Rates of liquid passage from the rumen were higher for alfalfa than for soybean hull-containing diets, and increased as alfalfa was added to the soybean hull diets. Solid passage rates also increased with increasing amounts of alfalfa in soybean hull-containing diets. Adding 30% alfalfa to primarily soybean hull diets led to positive associative effects on diet digestibility, but alfalfa additions increased liquid and solid passage rates, suggesting that the benefit was not a result of slower passage of soybean hulls from the rumen.
Keywords: Beef; Soybean hulls; Alfalfa; Steers; Digestion; Passage rate